New results on H∞ filter design for sampled‐data systems with packet dropouts and transmission delays. Issue 4 (1st June 2017) - Wang, Meng; Wang, Mao; Fu, Shasha; Qiu, Jianbin
Abstract : In this study, the problem of H ∞ filtering for sampled‐data systems under unreliable communication links is investigated. The phenomena of data packet dropouts and signal transmission delays are addressed in a unified framework. The objective is to design an admissible filter to guarantee the asymptotic stability of the filtering error system and minimise the H ∞ disturbance attenuation level. Thanks to the proposed novel Lyapunov–Krasovskii functional together with the improved Wirtinger's inequality and the reciprocally convex approach, novel sufficient linear‐matrix‐inequality‐based conditions are obtained for the existence and design of admissible filters. Finally, two simulation examples are provided to illustrate the efficiency and less conservativeness of the proposed H ∞ filter design methods.